Expression of intra- and extracellular granzymes in patients with typhoid fever. - de Jong, H; Garcia-Laorden, M; Hoogendijk, A; Parry, C; Maude, R; Dondorp, A; Faiz, M; van der Poll, T; Wiersinga, W (Public Library of Science, 2017)
Background Typhoid fever, caused by the intracellular pathogen Salmonella (S.) enterica serovar Typhi, remains a major cause of morbidity and mortality worldwide. Granzymes are serine proteases promoting cytotoxic lymphocytes mediated eradication of intracellular pathogens via the induction of cell death and which can also play a role in inflammation. We aimed to characterize the expression of extracellular and intracellular granzymes in patients with typhoid fever and whether the extracellular levels of granzyme correlated with IFN-γ release. Methods and principal findings We analyzed soluble protein levels of extracellular granzyme A and B in healthy volunteers and patients with confirmed S. Typhi infection on admission and day of discharge, and investigated whether this correlated with interferon (IFN)-γ release, a cytokine significantly expressed in typhoid fever. The intracellular expression of granzyme A, B and K in subsets of lymphocytic cells was determined using flow cytometry. Patients demonstrated a marked increase of extracellular granzyme A and B in acute phase plasma and a correlation of both granzymes with IFN-γ release. In patients, lower plasma levels of granzyme B, but not granzyme A, were found at day of discharge compared to admission, indicating an association of granzyme B with stage of disease. Peripheral blood mononuclear cells of typhoid fever patients had a higher percentage of lymphocytic cells expressing intracellular granzyme A and granzyme B, but not granzyme K, compared to controls. Conclusion The marked increase observed in extra- and intracellular levels of granzyme expression in patients with typhoid fever, and the correlation with stage of disease, suggests a role for granzymes in the host response to this disease.